Compact 1.75-2.7 GHz Tunable BPF With Wide Stopband Up to 9.5 GHz Using Harmonic-Controlled SIDGS Resonators - Tang, Deshan; Qian, Huizhen Jenny; Dong, Yuandan; Luo, Xun (IEEE transactions on circuits and systems. II, Express briefs, 2022)
In this brief, a harmonic-controlled substrate-integrated defected ground structure (SIDGS) resonator with tuning capacitor is proposed for the design of tunable filter. Such resonator exhibits a harmonic-controlled characteristic. The fundamental resonant frequency can be properly tuned, while the spurious resonance is controlled at much higher frequency to achieve a wide stopband. To verify the principle, a tunable bandpass filter (BPF) is designed and fabricated based on the resonator. The center frequency can be tuned from 1.75 to 2.7 GHz. Meanwhile, the stopband can extend up to 9.5 GHz with a rejection level of 20 dB for all tuning cases. The BPF also exhibits low insertion loss (i.e., 1.1-1.9 dB) and compact size (i.e., 0.07 {λ _{g}}\,\,{× }\,\,0.08\,\,{λ _{g}} , where {λ _{g}} is the microstrip guided wavelength at the 1.75 GHz).